2017
DOI: 10.1007/s00441-017-2624-x
|View full text |Cite
|
Sign up to set email alerts
|

Natriuretic peptide activation of extracellular regulated kinase 1/2 (ERK1/2) pathway by particulate guanylyl cyclases in GH3 somatolactotropes

Abstract: The natriuretic peptides, Atrial-, B-type and C-type natriuretric peptides (ANP, BNP, CNP), are regulators of many endocrine tissues and exert their effects predominantly through the activation of their specific guanylyl cyclase receptors (GC-A and GC-B) to generate cGMP. Whereas cGMP-independent signalling has been reported in response to natriuretic peptides, this is mediated via either the clearance receptor (Npr-C) or a renal-specific NPR-Bi isoform, which both lack intrinsic guanylyl cyclase activity. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Thus circulating CNP levels would be reflected by the sum of secreted CNP from these tissues. Furthermore, It is important to keep in mind that differential responses of CNP signaling pathways likely occur across tissues, resulting in different regulatory effects by CNP; for example, CNP suppresses ERK phosphorylation in chondrocytes [13,31], whereas it promotes ERK phosphorylation in pituitary cells [50]. Therefore, if CNP is positively regulated in some tissues and negatively regulated in other tissues, the sum of circulating NT-proCNP might not be changed.…”
Section: Discussionmentioning
confidence: 99%
“…Thus circulating CNP levels would be reflected by the sum of secreted CNP from these tissues. Furthermore, It is important to keep in mind that differential responses of CNP signaling pathways likely occur across tissues, resulting in different regulatory effects by CNP; for example, CNP suppresses ERK phosphorylation in chondrocytes [13,31], whereas it promotes ERK phosphorylation in pituitary cells [50]. Therefore, if CNP is positively regulated in some tissues and negatively regulated in other tissues, the sum of circulating NT-proCNP might not be changed.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our data suggest enhanced expression of NPR1 in feline pituitary tumour samples compared with normal feline pituitary tissue, which might indicate a potential regulatory role for ANP/NPR1 signalling in feline pituitary function. However, our expression data from mouse and rat pituitary tissue and cell lines support a potential role for CNP/NPR2, rather than ANP/NPR-1, in local regulation of pituitary function [ 10 , 11 , 12 , 51 ]. Moreover, mouse models of Nppa/Npr1 disruption do not phenocopy the growth-related phenotypes of Nppc/Npr2 models [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 88%
“…Such an inhibitory effect is at odds with previous studies suggesting that CNP and cGMP positively regulate GH secretion [ 22 , 23 ]. It may well be that activation of multiple signalling pathways downstream of the GC-B receptor could influence proliferation, and we have recently shown CNP-stimulated ERK1/2 activation to occur at concentrations several orders of magnitude below that required for cGMP generation [ 51 ]. An important caveat in interpreting our gene expression data from feline pituitary tumour samples is that surgical treatment of these patients results in the removal of the entire pituitary (hypophysectomy), rather than resection of tumour tissue [ 54 ]; as a result, these samples might contain some normal pituitary tissue as well as pituitary tumour tissue.…”
Section: Discussionmentioning
confidence: 99%
“…As cJun , Egr1 , Nr5a1 and Nr0b1 have all been shown to be transcriptionally regulated via the cAMP/PKA/CRE pathway [61,62,63,64], this represents a likely mechanism to explore in LβT2 cells. Additionally, we, and others, have previously shown that CNP can directly activate MAPK signalling in both rat pituitary tumour GH3 cells and LβT2 cells [65] or in melanoma cells [66]. Therefore, the differential effects of CNP on gene expression in LβT2 and αT3-1 cells could reflect differences in which signalling pathways are activated downstream of the GC-B receptor.…”
Section: Discussionmentioning
confidence: 90%